Hidrolisados pécticos na dieta de tilápia do Nilo e jundiá: implicações nutricionais e potencial prebiótico - Mombach, Patrícia Inês (2018)
The acquisition of new prebiotics from agroindustrial wastes aims to enhance the use of these byproducts, besides bringing benefits to animal nutrition. The objective of this study was to produce and characterize pectic hydrolysates from apple pomace and passion fruit peel and to investigate their prebiotic potential for Nile tilapia (Oreochromis niloticus) and silver catfish (Rhamdia quelen). In the first phase the pectin extraction from the residues was carried out, followed by the chemical hydrolysis process. The residues and their respective hydrolyzates were characterized as dry matter, total dietary fiber, soluble fiber, insoluble fiber, ash, crude protein and fat content. Hydrolysates were also analyzed for monosaccharide profile and physicochemical properties. In the second phase, two biological tests (Nile tilapia - 42 days and silver catfish - 49 days) were carried out to evaluate five test diets, one control diet and the other with addition of pectic hydrolysates (2.5 or 5 g/kg) apple pomace or passion fruit peel. At the end of the experimental periods, data and biological material were collected for performance evaluation, plasmatic, hepatic, enzymatic and histological parameters, body composition and evaluation of the intestinal contents of the fish. The results were submitted to the normality test, followed by analysis of variance, and the means of the treatments were compared by analysis of orthogonal contrasts at the 5% level of significance. The apple pomace and the passion fruit peel were promising for pectin extraction, resulting in hydrolysates with a high concentration of soluble fiber. In the analysis of the monosaccharides, the apple pomace hydrolyzate showed similar amounts of glucose-xylose-galacturonic acid (14.7, 13.5 and 16.11%). The apple pomace hydrolyzate showed high capacity to bind to water, a characteristic that is reduced in the passion fruit peel hydrolyzate. The production of short chain fatty acids at the intestinal level was influenced by the pectic hydrolysates, and the Nile tilapia juveniles presented higher production of acetic acid, with an influence on the hepatic glucose concentration. The silver catfish juveniles presented higher production of butyric acid, related to the count of goblet cells at intestinal level. For Nile tilapia, supplementation with passion fruit peel hydrolyzate (2.5 or 5 g/kg) provided lower body fat content, ensuring a healthier food with greater shelf stability. Pectic hydrolysates caused alterations in intestinal histological parameters, where Nile tilapia juveniles obtained greater benefits with the supplementation of passion fruit peel hydrolyzate (2.5 and 5 g/kg), which ensured a greater cell renewal, a higher absorption capacity of nutrients and maintenance of intestinal integrity, and silver catfish juveniles presented higher goblet cell counts with the supplementation of 2.5 g/kg of apple pomace hydrolyzate. The pectic hydrolysates of apple pomace and passion fruit peel, added to the diet of Nile tilapia and silver catfish juveniles allowed for satisfactory results, however, further studies should be carried out in order to define levels that allow greater gains in fish nutrition.